Factors that influencing payment disputes in subcontracting procurement / Aiman Haiqal Azmi and Nur’Ain Ismail - Azmi, Aiman Haiqal; Ismail, Nur’Ain (2019)
Construction disputes are common in the industry because involvement of various parties in a project. Because of that, the dispute occurs especially for payment to the subcontractors. Payment disputes occurs when a business have been provided by one side, but the other side refuse to pay the amount based on the work done by the other side. Even though our government has introduced many rules and obligation that have in form of subcontract to solve the problem of payment disputes, there are still many cases where the sub-contractors received the payment late than usual. The objective of this research is to identify the main factors of payment disputes from the main contractor to the subcontractors in the subcontracting procurement. The target respondent for this research is subcontractors from the grade G7 at the Klang, Selangor. The result was in form of descriptive statistics where the mean of each variable was identified by analyzing the data with the latest version of SPSS 25. The result indicates that factors influencing payment disputes is different by each party involved. This paper can contribute to the main factors towards the payment disputes in subcontracting procurement.